PENGABDIAN MASYARAKAT EKONOMI KESEHATAN PESANTREN MELALUI POS KESEHATAN PESANTREN - Mohammad Labib; Ahmad Muchlis; Yusri Hapsari; Rony Edward Utama; Iin Listiawati; Dhea Charientania Eryanti (LPPM Universitas Bina Bangsa, 2023)
Islamic boarding schools in Indonesia still have many classic problems, namely cleanliness and health. This can happen because Islamic boarding schools rarely provide clean and healthy lifestyle education. The reason for selecting the topic or the importance of this community service topic is because many health problems in Islamic boarding schools are still not good. The service method begins with conducting a survey to observe the existing situation, after which it is continued with an approach and seeks approval from the leadership to hold several activities at the Baitul Qurro' Jakarta Islamic boarding school, namely counseling on Clean and Healthy Behavior and strengthening the functions of the Poskestren. Results and discussion: On July 15, 2023 the implementation of counseling and health checks for a clean and healthy lifestyle individually and in the Islamic boarding school environment went well and smoothly. This activity was carried out with a community service team at the Baitul Qurro' Islamic boarding school, Jakarta. The counseling was attended by all Baitul Qurro' Jakarta Youth Red Cross (PMR) teams